Introduction to early childhood education : preschool through primary grades - Brewer, Jo Ann. (Boston : Pearson/Allyn & Bacon, 2007)
The primary goal of this text is to provide a comprehensive knowledge base for teachers of young children so they can make decisions that are founded on more than educational traditions or their own experiences as students. This text is also designed to encourage early childhood teachers to consider the child, the family, and the community when planning experiences for each individual. Finally, this text will help readers prepare for the Praxis Exam, which some states require teachers [to] pass before they can become certified.-Pref.
Includes bibliographical references and index.
Keywords: arly childhood education -- United States; Early childhood education -- History; Child development -- United States